Investigation of the zero-charge point of orange biomass for further use as a metal biosorbent - Stadnik, Jucieli; Giusti, Edneia Durli; Borges, Aline Rocha (Seven Editora, 2023)
Biosorption is characterized by the removal, retention, or recovery of metals present in toxic residues, through the adsorbent and adsorbate. For this, one of the characteristics to be evaluated in the determination of a good biosorbent is the zero-charge point. This value is defined by the pH value at which the biomass surface has a neutral charge, that is, the adsorption of H+ and OH- ions is equal. For the orange species studied, the values of the zero-charge point form between pH 4.5 and pH 5.8.DOI:https://doi.org/10.56238/alookdevelopv1-103